2022
DOI: 10.3389/fmed.2022.922239
|View full text |Cite
|
Sign up to set email alerts
|

Value of transbronchial needle aspiration combined with a rapid on-site evaluation of cytology in the diagnosis of pulmonary lesions

Abstract: BackgroundThe diagnostic value of rapid on-site evaluation (ROSE) of cytology during endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) remains controversial. The purpose of this study was to validate the value of ROSE during the EUBS-TBNA procedure in the diagnosis of pulmonary lesions (PLs).MethodsEnrolled in this study were 260 patients with nodules, masses, cavities, or inflammatory lesions on pulmonary CT images. They were assigned to undergo EBUS-TBNA with ROSE (n = 134) or with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Observations on 328 cases revealed that the ROSE and the ultimate cytologic diagnoses agreed on 91.6% of lymph nodes ( p < .001) 10 . Liang et al analyzed 260 cases with lung masses, nodules, cavities, and inflammatory lesions who underwent EBUS‐TBNA with ROSE ( n = 134) or without ROSE ( n = 126) 11 . The specificity, sensitivity, NPV (negative predictive value) and PPV (positive predictive value) of the ROSE‐guided EBUS‐TBNA were 96.9, 97.4, 98.90% and 92.5, respectively 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations on 328 cases revealed that the ROSE and the ultimate cytologic diagnoses agreed on 91.6% of lymph nodes ( p < .001) 10 . Liang et al analyzed 260 cases with lung masses, nodules, cavities, and inflammatory lesions who underwent EBUS‐TBNA with ROSE ( n = 134) or without ROSE ( n = 126) 11 . The specificity, sensitivity, NPV (negative predictive value) and PPV (positive predictive value) of the ROSE‐guided EBUS‐TBNA were 96.9, 97.4, 98.90% and 92.5, respectively 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al analyzed 260 cases with lung masses, nodules, cavities, and inflammatory lesions who underwent EBUS‐TBNA with ROSE ( n = 134) or without ROSE ( n = 126) 11 . The specificity, sensitivity, NPV (negative predictive value) and PPV (positive predictive value) of the ROSE‐guided EBUS‐TBNA were 96.9, 97.4, 98.90% and 92.5, respectively 11 . In our study, we obtained similar fidelities with 90,2%, 93,1%, 94,8%, 87,1%, and 91,4% rates for sensitivity, specificity, PPV, NPV, and accuracy, respectively.…”
Section: Discussionmentioning
confidence: 99%